Do faba bean (Vicia faba L.) accessions from environments with contrasting seasonal moisture availabilities differ in stomatal characteristics and related traits? - Khazaei H; Street K; Santanen A; Bari, A.; Stoddard FL (Springer, 2013)
Drought is a major constraint to faba bean (Vicia faba L.) production, and there are many mechanisms by which leaves can regulate water loss. Our primary objective was to test if the origin of the faba bean accessions, from drought-prone and non-drought-prone environments, was associated with differences in measurable aspects of stomatal morphology and physiology related to water use. Two sets, each consisting of 201 faba bean accessions, were chosen from environments with contrasting seasonal moisture profiles following the focused identification of germplasm strategy (FIGS), and then screened under well watered conditions. From these, two subsets of 10 accessions each were chosen to test for differences in response to drought. Parameters related to stomatal function and water status were measured. The dry-adapted set had bigger stomata, higher leaf relative water content (LRWC) and cooler leaves under well watered conditions. Stomatal density and stomatal area per unit area of leaflet were negatively correlated with gas exchange parameters and positively correlated with intrinsic water use efficiency. Drought caused stomatal densities to increase in the dry set while stomatal length decreased in both sets. The moisture deficit was sufficient to decrease gas exchange in both sets to similar levels, but the dry-adapted set maintained warmer leaves and a higher LRWC that showed no significant correlations with leaf morphology or gas exchange, demonstrating more effective stomatal regulation. The results also support that collection site data from the environment where genetic resources are collected can be used as indicators of adaptive traits in an herbaceous annual species.